2019
DOI: 10.1109/lawp.2019.2931450
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Receiving Phase-Modulated Signals With a Rydberg Atom-Based Receiver

Abstract: Recently, we introduced a Rydberg-atom based mixer capable of detecting and measuring the phase of a radiofrequency field through the electromagnetically induced transparency (EIT) and Autler-Townes (AT) effect. The ability to measure phase with this mixer allows for an atom-based receiver to detect digital modulated communication signals. In this paper, we demonstrate detection and reception of digital modulated signals based on various phase-shift keying approaches. We demonstrate Rydberg atom-based digital … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…There is a slight dip in beat note signal strength when the probe laser frequency sits on the top of the AT peak. One advantage of having the vapor cell embedded inside the PPWG antenna (as opposed to having the LO and SIG transmitted from the same location as was done in [25] and [29]) is that it allows one to easily change the LO field at the atoms by varying the input power to the PPWG antenna. That is, the embedded sensor head allows one to easily vary the LO E-field to find the optimal value for the LO/SIG ratio in order to maximize the beat note signal strength.…”
Section: B Beat Note Signal From the Mixermentioning
confidence: 99%
See 1 more Smart Citation
“…There is a slight dip in beat note signal strength when the probe laser frequency sits on the top of the AT peak. One advantage of having the vapor cell embedded inside the PPWG antenna (as opposed to having the LO and SIG transmitted from the same location as was done in [25] and [29]) is that it allows one to easily change the LO field at the atoms by varying the input power to the PPWG antenna. That is, the embedded sensor head allows one to easily vary the LO E-field to find the optimal value for the LO/SIG ratio in order to maximize the beat note signal strength.…”
Section: B Beat Note Signal From the Mixermentioning
confidence: 99%
“…While the configuration in Fig. 1 is for the case where both the LO and SIG are applied via the same horn [29], the LO and SIG can also be applied with two different horns [25]. The problem with both these configurations is that they require the LO to be transmitted alongside the SIG.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [15,16] investigated the feasibility of this atom-based receiver over a continuously tunable RF-carrier; the authors showed that the communication at a rate of 500 kbps can be reliably performed within a tunable bandwidth of 200 MHz near a 10.22 GHz carrier. Holloway et al [17] observed that the receiving system based on Rydberg atoms can detect and demodulate binary-phase-shift-keying (BPSK), quadrature-amplitude-modulation (QAM), and quadrature-phase-shift-keying (QPSK) signals. Due to numerous available resonant frequencies of the Rydberg states from 100 MHz to sub-THz, it is possible to achieve the broadband communication by changing the coupling frequency between RF E-field and the Rydberg States.…”
Section: Introductionmentioning
confidence: 99%
“…This Rydberg-atom based sensor can act as compact reciever/antenna, enabling quantum-based receivers to be used in communication applications to detect and receive modulated signals [21][22][23][24][25][26][27][28] . This has led to the new term "atom-radio" 26,29 .…”
mentioning
confidence: 99%
“…A Rydbergatom receiver has a bandwidth of about 1 MHz to 5 MHz 25,27,28,30 . This bandwidth limit is due to the time required to populate the atoms to a Rydberg state 25,27 . Since music is limited to 20 kHz in frequency, the Rydberg-atom based recorder can capture the full musical range of the instrument with high fidelity.…”
mentioning
confidence: 99%